When an uncommon condyloma revealed a multiple myeloma: Case report. (October 2021) - Bouabdella, Sara; Aouali, Soraya; Ragragui, Hanan; Zizi, Nada; Dikhaye, Siham
Abstract: Introduction and importance: Condyloma are a common and easily diagnosticated condition that could affect the area around and inside the anus. But a nodular perianal lesion is not always a simple condyloma. Case presentation: We report a case of a 61-year-old patient with nodular perianal lesions mimicking condyloma that has revealed an amylosis and a multiple myeloma. Clinical discussion: The cutaneous manifestations of amyloidosis are diverse. Perianal nodular lesions were indicative of cutaneous amyloidosis in our patient. It is imperative to screen systemic involvement for amyloidosis. Conclusion: Our case report highlights the importance of minitious physical examination because some simple lesions can hide dangerous affections. Highlights: A nodular perianal lesion is not always a simple condyloma. Cutaneous amyloidosis could be manifested by a nodural perianal lesion. Some simple cutaneous lesions can hide dangerous affections.